(untitled) (Resenhas do Instituto de Matemática e Estatística da Universidade de São Paulo, 2014)
In this paper we use a statistical method to provide estimations of the relative frequency for such regions. We also give estimations of the relative frequencies for the regions of phase portraits having nodes, foci and limit cycles.